Deriving Weights for Additivity of Chained Volume Measures in the National Accounts - Jesus C. Dumagan (Philippine Institute for Development Studies (PIDS), 2011)
In current practice in all countries, subaggregate chained volume measures (CVMs) are not weighted and, thus, not additive. However, weights are necessary because without them, nonadditivity permits the nonsensical result that a subaggregate CVM could exceed the aggregate CVM. This paper derives weights to make the sum of weighted subaggregates equal the aggregate (i.e., additivity) and avoid this nonsensical result. The weights are ratios of subaggregate to aggregate chained price deflators that exceed, equal, or fall below 1 depending on relative prices. CVMs in current practice are additive only in the special case of constant relative prices when all weights equal 1. Without weights, they are not additive when relative prices change and, in this case, empirical results show that nonadditivity could significantly distort the sectoral composition of GDP.
Keywords: C43; 330; chained volume measure; GDP in chained prices; additivity weight; chained index; consistency in aggregation; Nationaleinkommen; Volkswirtschaftliche Gesamtrechnung; Philippinen